FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI KONSUMEN PADA KOMUNITAS MEREK TOYOTA YARIS CLUB INDONESIA DENGAN INTERAKSI PREFERENSI SEBAGAI VARIABEL MODERASI - , Arief Budiman, Dr. Shellyana Junaedi, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The increasingly fierce market competition will indirectly affect a company in maintaining its market share. In order to survive in the competition then the producers demanded more attention to the needs and desires of consumers, especially on a strategy to maintain the loyalty of consumers. In general, loyal customers are not looking for alternatives and not easily turn to other brands of products. For that reason the company sought to create a loyal customer. Current for all categories of products provide a brand identity for each product. Function of the brand is not just a simple name or a differentiator with competitors' products, but has become an important factor in competitive advantage. Brands can simplify the decision, offering quality assurance and reduce risk, help the expression of self, and offer friendship and fun. In addition the brand has become a crucial element contributing to the success of a marketing organization, whether business or nonprofit enterprise, manufacturing and service providers, and local and global organizations. This study related to the Woisetschlager in 2008 which states that there are several dimensions that affect the antecedent of consumer participation within the community that the community identification, community satisfaction and the degree of influence and some of the dimensions of the consequences that occur because consumer participation is brand image, loyalty and the Word of MouthUsing multiple regression analysis, the study found that all attributes were significantly influence antecedent of consumer participation and consumer participation significantly affect the consequences of attributes. The interaction with the higher preference level of consumer participation in it.